Understanding the multi-seasonal spectral and biophysical characteristics of reedbed habitats in the UK. Issue 4 (1st October 2016) - Onojeghuo, Alex O.; Blackburn, George A.
Abstract: Reedbed in the UK has been classified as priority habitat for most regional Biodiversity Partnerships. However, critical information pertaining to the quality and spatial coverage of reedbed is currently lacking. This paper presents the results of a project conducted in collaboration with the Cumbria Wildlife Trust and Environment Agency aimed at monitoring and understanding variations in the spectral reflectance and biophysical properties of reedbed canopies across Leighton Moss Nature Reserve in Lancashire, northwest England. Throughout the seasonal phenological cycle of the reedbed habitats in the study area, optimal spectral indices required for quantifying its biophysical properties were determined using field spectroscopy and ground-based measurements. Results of the experiment showed that the narrow-band-derived Difference Vegetation Index (DVI) and Renormalised Difference Vegetation Index (RDVI), with the correlation coefficient R 2 of 0.77 and 0.72, respectively, provided the most accurate estimates of the leaf area index for the reedbed canopies.